Genomic alterations related to HPV infection status in a cohort of Chinese prostate cancer patients - Lang, Bin; Cao, Chen; Zhao, Xiaoxiao; Wang, Yi; Cao, Ying; Zhou, Xueying; Zhao, Tong; Wang, Yuyan; Liu, Ting; Liang, Wenjia; Hu, Zheng; Tian, Xun; et al. (European journal of medical research, 2023)
Human papillomavirus (HPV) has been proposed as a potential pathogenetic organism involved in prostate cancer (PCa), but the association between HPV infection and relevant genomic changes in PCa is poorly understood. To evaluate the relationship between HPV genotypes and genomic alterations in PCa, HPV capture sequencing of DNA isolated from 59 Han Chinese PCa patients was performed using an Illumina HiSeq2500. Additionally, whole-exome sequencing of DNA from these 59 PCa tissue samples and matched normal tissues was carried out using the BGI DNBSEQ platform. HPV infection status and genotyping were determined, and the genetic disparities between HPV-positive and HPV-negative PCa were evaluated. The presence of the high-risk HPV genome was identified in 16.9% of our cohort, and HPV16 was the most frequent genotype detected. The overall mutational burden in HPV-positive and HPV-negative PCa was similar, with an average of 2.68/Mb versus 2.58/Mb, respectively, in the targeted whole-exome region. HPV-negative tumors showed a mutational spectrum concordant with published PCa analyses with enrichment for mutations in SPOP, FOXA1, and MED12. HPV-positive tumors showed more mutations in KMT2C, KMT2D and ERCC2. Copy number alterations per sample were comparable between the two groups. However, the significantly amplified or deleted regions of the two groups only partially overlapped. We identified amplifications in oncogenes, including FCGR2B and CCND1, and deletions of tumor suppressors, such as CCNC and RB1, only in HPV-negative tumors. HPV-positive tumors showed unique deletions of tumor suppressors such as NTRK1 and JAK1. The genomic mutational landscape of PCa differs based on HPV infection status. This work adds evidence for the direct involvement of HPV in PCa etiology. Different genomic features render HPV-positive PCa a unique subpopulation that might benefit from virus-targeted therapy.